2004
DOI: 10.1063/1.1695357
|View full text |Cite
|
Sign up to set email alerts
|

On nonlinear plasma instabilities during the substorm expansive phase onset

Abstract: Using a stability analysis based on a Lagrangian–Hamiltonian approach to magnetohydrodynamics, this paper addresses the stability of the Earth’s magnetotail during the later stages of the growth phase of the substorm. The analysis shows that the magnetotail at about 10–12RE is the likely region for instability. Furthermore, the analysis helps to explain why the substorm intensification begins on field line mapping from the Earthward edge of the substorm plasma sheet to auroral arcs near the equatorward edge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…2K). This sequence is in agreement with several previous studies and the inside-out model of substorm onset (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
supporting
confidence: 81%
“…2K). This sequence is in agreement with several previous studies and the inside-out model of substorm onset (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
supporting
confidence: 81%
“…The NENL model asserts that the magnetic reconnection initiated outside 15 R E in the magnetotail produces fast bursty bulk plasma flows which arrive at the near-Earth region with flow braking to cause substorm onset (e.g., Angelopoulos et al, 1992;Shiokawa et al, 1998). The near-Earth onset model proposes that some instabilities are initiated in the near-Earth plasma sheet to cause substorm onset and subsequent expansion (e.g., Lui et al, 1991;Roux et al, 1991;Samson et al, 1992;Cheng and Lui, 1998;Lee et al, 1998;Cheng and Zaharia, 2004;Cheng, 2004;Dobias et al, 2004;Lui, 2004;Saito et al, 2008). In particular, the theoretical calculation of ballooning instability in the 3-D magnetospheric equilibrium that models the growth phase magnetosphere showed that the low-frequency instability in the Pi2 frequency range has the maximum growth rate in the strong cross-tail current region, and the most unstable ballooning mode field line region can be traced to the ionosphere in the transition region between the Region 1 and Region 2 currents (Cheng and Zaharia, 2004;Cheng, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Various plasma instabilities have been proposed as playing important roles during the substorm onset process. These include the tearing [Schindler, 1974;Sitnov et al, 1997;Zelenyi et al, 2008], ballooning [Cheng and Lui, 1998;Bhattacharjee et al, 1998;Dobias et al, 2004;Zhu et al, 2003;Saito et al, 2008;Friedrich et al, 2001], lower hybrid drift [Shinohara et al, 1998;Yoon et al, 2002;Mok et al, 2006], Kelvin-Helmholtz [Rostoker and Samson, 1984;Dobias et al, 2006], and the ion Weibel [Yoon and Lui, 1993;Sadovskii and Galeev, 2001] instabilities.…”
Section: Introductionmentioning
confidence: 99%